The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15593/perm.mech/2021.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 2-D and 3-D modelling of dovetail joint of composite fan blade for choosing rational reinforcement schemes

Abstract: Turbofan jet engines are among the most complex and responsible constructions in the world. The creation of modern globally competitive engines is impossible without the use of digital twin technologies: a set of computational models that fully describe the behaviour of the structure under any operating conditions. Today, composite materials are widely used in many industries. In aircraft engines, their use is very promising for fan blades and fan case to reduce the overall weight of the engine and inertial lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…At the same time, the experimental data indicated that through-thickness compression could significantly increase the interlaminar shear strength of the laminates [8]. Not considering this fact can lead to decreases in the weight efficiency of the composite structure [9].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…At the same time, the experimental data indicated that through-thickness compression could significantly increase the interlaminar shear strength of the laminates [8]. Not considering this fact can lead to decreases in the weight efficiency of the composite structure [9].…”
Section: Introductionmentioning
confidence: 91%
“…The FE mesh was refined between the notches. The 0.25-mm FE size in the gauge section of the specimen was chosen by a mesh convergence study, similarly to [9]. The total number of finite elements was 92,480.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Composite materials also find their application in the manufacturing of fan blades for aircraft engines [6][7][8].…”
Section: Introductionmentioning
confidence: 99%